M-lump solutions and interactions phenomena for the (2+1)-dimensional KdV equation with constant and time-dependent coefficients - Ali, Karmina K.; Yilmazer, Resat (Elsevier, 2022)
In this paper, Hirota's simple method and long-wave method are used to study the (2+1)-dimensional KdV equation including constant and time-dependent coefficients. One-, two-, and three-M-lump solutions are constructed for both cases. Also, the interaction phenomena of M-lump solution with one-soliton, and two-soliton waves are derived for these equations. Moreover, to investigate the physical characteristics of the obtained results, the 3-dimensional figures and contour plots are graphed. All gained solutions verify the proposed equations.
Keywords: Hirota's simple method; M-lump solutions; Interaction solutions